2022
DOI: 10.3390/foods11040521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination of Time and Temperature on Quality Characteristics of Sous Vide Chicken Breast

Abstract: The use of minimal thermal processing techniques such as sous vide technology to improve the quality of meat-based foods has gained a special focus in recent years. A proper combination of temperature and time parameters in sous vide processing plays an important role in the water-holding capacity, texture properties, and juiciness of the meat. The present study aimed to assess the impact of the one-step and two-step sous vide processing on different quality properties of chicken breast with special emphasis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Similarly, Miranda et al [ 38 ] reported 1–3 log CFU/g Enterococcus counts in raw poultry meat (chicken and turkey). These results showed that the two-step sous vide technique was sufficient to produce safe cooked chicken breasts that had higher quality attributes compared to those of one-step sous vide [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Miranda et al [ 38 ] reported 1–3 log CFU/g Enterococcus counts in raw poultry meat (chicken and turkey). These results showed that the two-step sous vide technique was sufficient to produce safe cooked chicken breasts that had higher quality attributes compared to those of one-step sous vide [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the end of both the chilled and mild chilled storage, the TBARS values of two-step sous vide chicken breasts were significantly lower than the one-step-sous-vide-treated ones ( p < 0.05). This can be explained by the low oxidation rates of the chicken breast after being cooked with low temperature treatments at day 0 compared to the traditional sous vide one [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were analyzed using a texture profile analysis (TPA) to evaluate the texture of the chicken, following the method applied by Endrit, with minor modifications (Hasani et al, 2022). The P-35 cylinder probe and texture analyzer (Model TMS-Pilot, FTC) were used the procedure was as follows: compress the chicken to 50% of its original height in two cycles at a speed of 1 mm/s (velocity of 100 N) to obtain a force-time curve.…”
Section: Texturementioning
confidence: 99%
“…Among the research papers published in this Special Issue, “Effect of Combination of Time and Temperature on Quality Characteristics of Sous Vide Chicken Breast” was investigated by a research team [ 1 ]. This paper showed that chicken breast treated with a two-step temperature (50 and 60 °C) had an improved texture, lower cooking loss, acceptable redness values, and reduced lipid oxidation as compared with the samples cooked at the one-step temperature of 60 °C.…”
mentioning
confidence: 99%